San Marcos and the study of Amazonian indigenous languages - Solís Fonseca, Gustavo (2000)
The initial interest in the study of Amazonian languages is to a large extent a direct consequence of the needs of missionary work, which is why the first religious of the colonial period, mainly the Jesuits and the Franciscans, were concerned with learning these languages. Among these two orders, the Society of Jesus clearly stands out, since, among other merits, one of its members - Joseph de Anchieta - wrote the first grammar of an indigenous Amazonian language, Tupinimbá, of the Tupi-Guarani linguistic family, spoken on the Atlantic coasts in Brazilian territory.